Ayurvedic protocols of chronic pain management: spatiotemporality as present moment awareness and embodied time - Vinita Agarwal (Frontiers in Pain Research, 2024)
BackgroundTemporality is understood as the subjective perception of the flow of chronological time and is a central component of contemporary and integrative medicine approaches. Although temporal dynamics are recognized as central to the processes associated with chronic pain (CP), the temporal management of CP is inadequately understood in pain research.Research questionHow is temporality conceptualized in Ayurvedic protocols of CP management?.MethodAyurvedic physicians (N = 10) from India were recruited through purposive and snowball sampling. A semi-structured interview protocol was employed to gather qualitative data focusing on the Ayurvedic protocol employed to treat CP patients. The interviews were audio-recorded, professionally transcribed, and thematically analyzed. Member validation, participant voice, and researcher self-awareness were employed to strengthen reliability and validity.FindingsAn ontologically grounded thematic exploration of Ayurvedic protocols illustrates that temporality is conceptualized in CP as spatiotemporal present moment awareness (PMA) and embodied time (ET). Spatiotemporality as PMA references an awareness of the relationality of cognitive temporal movement, dosha operations, and their pathophysiological expression in the body. Spatiotemporality as ET is conceptualized as awareness of the expression of time in embodied emotional and psychosocial processes as in the movement of the breath through the body, the movement of body sensations over time, and in their intersection with consciousness.DiscussionThe study findings present an experiential and relational framework situating spatiotemporality ontologically as an organizing principle in CP management. While temporality focuses on the representation of experiences and relations over time, spatiotemporality foregrounds a constructionist approach by centering the embodied spatial cognitive expression of time, consciousness, and subjective experience.